Perceived Environmental Uncertainty: Effects of Information and Structure - Huber, George P.; O’Connell, Michael J.; Cummings, L. L. (Academy of Management Journal, 1975)
The effects of environmental information (load and specificity) and group structure on perceived environmental uncertainty were studied. Significant main effects were found for information load and group structure. Interaction effects suggest explanations of variance in perceived uncertainty are much more complex than those suggested in the literature.